1998
DOI: 10.1002/(sici)1098-2752(1998)18:2<125::aid-micr11>3.3.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

End‐to‐end versus end‐to‐side arterial anastomosis patency in microvascular surgery

Abstract: The patency rates of microsurgical end-to-end and end-toside anastomosis in the rat carotid artery were studied. Seventy end-to-end and seventy end-to-side arterial anastomoses, using 10-0 nylon interrupted sutures, were performed on 140 Sprague-Dawley rats. Findings indicated 100% patency in end-to-end as well as end-to-side immediately and 1 week post-anastomosis. This investigation suggests that there is no significant advantage between the methods studied based on vessel patency alone. The decision to perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 0 publications
2
18
0
4
Order By: Relevance
“…In the anastomoses of end-to-side, the success rate generally depends on the suitable implementation of arteriotomy at the correct location. A sudden change in vessel diameter can result in turbulence, which may cause thrombosis (Sen et al, 2006;Dotson et al, 1998). Also, vasospasms decrease in endto-side anastomoses, cessation, or low drop associated with vasospasm might be prevented in OSA as well (Dotson et al, 1998;Verhelle and Heymans, 2005;Yoleri and Songur, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…In the anastomoses of end-to-side, the success rate generally depends on the suitable implementation of arteriotomy at the correct location. A sudden change in vessel diameter can result in turbulence, which may cause thrombosis (Sen et al, 2006;Dotson et al, 1998). Also, vasospasms decrease in endto-side anastomoses, cessation, or low drop associated with vasospasm might be prevented in OSA as well (Dotson et al, 1998;Verhelle and Heymans, 2005;Yoleri and Songur, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…12 Common carotid arteries are easily accessible and have adequate vessel size and patency. 12 Common carotid arteries are easily accessible and have adequate vessel size and patency.…”
Section: Methodsmentioning
confidence: 99%
“…Both rat microsurgery studies and human vascular surgery studies have shown no differences in patency rates between end-to-end and end-to-side anastomoses. [34][35][36] As the number of procedures and surgical approaches evolve, selection criteria will vary among surgeons, based on personal preferences and complex patient and donor presentations.…”
Section: Planning Vascular Anastomosesmentioning
confidence: 99%